Instruction on questioning teaching style, student question level and achievement in physics - Aban, Lorna Constantino (2006)
The study was conducted to determine the effect of different teaching methods such as the traditional teaching style with instruction on questioning (TWI), traditional teaching style without instruction on questioning (TWOI), and facilitating teaching style without instruction on questioning (FWOI), on the student question level and achievement in physics. It utilized the quasi-experimental method as well as several researcher-made instruments content-calidated by physics and education experts. A significant low positive correlation exists between student question level and achievement in physics. TWI and FWOI teaching methods significantly enhanced the achievement of students in physics. Since FWOI significantly affected the achievement of students, this teaching style should always be used.
Thesis (M.A. Physics Education)--University of the Philippines, Diliman.
Keywords: Physics -- Study and teaching (Higher) -- Philippines -- Bayombong (Nueva Vizcaya); Academic achievement -- Bayombong (Nueva Vizcaya)